Le métier impossible des moniteurs de Maison Familiale Rurale : analyse de l’activité, entre l’audace d’un projet et la réalité du terrain - Violaine Charil (Recherches en Éducation)
At a time where the labour organization is sometimes blamed, where management processes are thoroughly observed, we've wanted to examine an unrecognized organization: the MFR and especially focus on teachers who are in the core of this organization. Those people are also called instructors because their assignments are various and go further than simple teaching, giving some knowledge some know-how or some manners. Nowadays, educating and teaching are often classed in impossible works. So MFR instructor’s form a part of those impossible works. In our research works, which register in professional didactic frame, we've taken an interest in the way that those instructors organize their goals conceding they're meticulous organizer of their activity. So we've chosen a methodology of activity analysis which gather the double instruction technique (dear to Y. Clot), and the critical incidents methodology developed in ergonomics by J. Leplat. Our results lead us to pose some new questions linked to the evolution of labour organization within MFR and by the society evolution. Then, this helps us to admit the importance of collective and team work in that kind of organization.